The influence of sustainability accounting, organizational culture, and transformational leadership on organizational performance in the digital era - Astrid Julivanti Posawa; Agoestina Mappadang (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2025)
This study aims to determine the effect of the application of sustainability accounting, organizational culture, and transformational leadership on organizational performance in the digital era. The study uses primary data obtained from questionnaires distributed to respondents. The sample size is 688 employees from mining companies operating in Southeast Sulawesi Province. The results of this study show that the application of sustainability accounting, organizational culture, and transformational leadership positively affects organizational performance. Public interest statements This study highlights the importance of sustainable accounting, organizational culture, and transformational leadership in improving organizational performance, especially in mining companies in Southeast Sulawesi. The findings emphasize that strong leadership, sustainable practices, and a positive work culture are key drivers of success in the digital era. These insights can guide companies and policymakers in fostering more responsible and effective organizational strategies.